If f(x) = 4 - x2 and g(x) = 6x, which expression is equivalent to (g-1)(3)?

A. 6-3-(4+3)^2

B. 6-3-(4-3)^2

C. 6(3)-4+3^2

D. 6(3)-4-3^2

Respuesta :

For this case we have the following functions:

[tex]f (x) = 4-x ^ 2\\g (x) = 6x[/tex]

We must find[tex](g-f) (3)[/tex].

By definition we have to:

[tex](g-f) (x) = g (x) -f (x)[/tex]

So:

[tex](g-f) (x) = 6x- (4-x ^ 2) = 6x-4 + x ^ 2[/tex]

So, we have to for[tex]x = 3:[/tex]

[tex](g-f) (3) = 6 (3) -4+ (3) ^ 2[/tex]

Answer:

The correct option is C

[tex]6 (3) -4+ (3) ^ 2[/tex]